PENGGUNAAN MEDIA BERBASIS TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI - Andria Rosa; Mahyudin Ritonga; Wedy Nasrul (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2020)
The study of the problems in this study is about the problems faced by teachers in the use of learning media. The purpose of the research is to describe the ability of teachers to use technology-based media, what media teachers use in the learning process, and what problems teachers face in using technology-based learning media. This research is field research that uses qualitative descriptive methods, namely by describing the object of research as it is. The subjects of this study are Principals, PAI Teachers and Students. Data collection methods use observation, interview and study documentation. In examining the validity of the data that the author can in the field, the author uses triangulation techniques namely; triangulation of sources, triangulation techniques and triangulation of time. The findings show that: first, Teachers are able to accompany the development of the times in using technology-based media on islamic education learning, only that they do not apply the skills they have to the teaching learning process. Second, On learning devices, Islamic Religious Education teachers already use technology-based learning media although it has not varied, but in the reality in the field they only teach conventionally. Third, the problems faced by teachers do not always have a major effect on students' learning outcomes. Teachers can carry out their duties properly even if not fully supported by learning media